Archaeozoological research in Medieval Iberia: fishing andfish trade on Almohad sites - Morales Muniz, Arturo; Roselló Izquierdo, Eufrasia; Lentacker, An; Morales Mufiiz, Dolores Carmen (Trabalhos de Antropologia e Etnologia, 2020)
.